METHODICAL SIGNIFICANCE OF TEACHING GIFTED STUDENTS (Education of gifted children) - Ma`sud Djabborov Bahriddinovich (Galaxy International Interdisciplinary Research Journal, 2023)
A broad group of special practices, procedures and theories used to train children identified as gifted education, talented and talented programs (TAG), or G/ T education. The enrichment program teaches additional, relevant materials but ensures that the student develops at the same pace as other students in the curriculum. For example, once gifted students have completed the usual work in the curriculum, the enrichment program can provide them with additional information about the topic. The acceleration program will develop the reader faster than usual under the usual curriculum. This is done through many different approaches.